(untitled) (Journal SCIENCEVOLUTION, 2025)
This study aimed to analyze the simulation of atmospheric pollutant dispersion generated by mining activities at Cerro El Toro and La Arena, located in Huamachuco, Peru, during 2022. A quantitative approach with a descriptive, cross-sectional design and applied research type was employed. The technique used was indirect observation through the processing of atmospheric data in the HYSPLIT model, enabling the estimation of the trajectory, area, and distance reached by PM2.5, PM10, and SO2 pollutants. Results showed the predominant wind direction was from east to west. In both cases, pollutant concentrations exceeded national reference values, reaching distances less than 7.84 km and areas up to 1,904 ha. Cerro El Toro demonstrated a greater impact on populated areas, while at La Arena, the effects were confined to the surrounding ecosystem. It is concluded that the dispersion of these pollutants constitutes a potential risk to public health and the environment, especially in inhabited areas near mining operations lacking permanent atmospheric monitoring.